STUDY OF FETAL HEMOGLOBIN WITH GESTATIONAL AGE, BIRTH WEIGHT AND RETINOPATHY OF PREMATURITY IN PRETERM INFANTS - Prasad, Nishi; Dubey, Aditi; Kumar, Kavita; Shrivastava, Jyotsna (Indonesian Vitreoretinal Society, 2023)
ABSTRACT Introduction: The objective of this study was to find an association of fetal hemoglobin (HbF) with gestational age, birth weight and retinopathy of prematurity (ROP) in preterm infants. Methods: Observational prospective study. We included a total of 410 preterm infants with <36 gestational weeks and <2.5 kg birth weight, in a tertiary care hospital of central India for a period of one year. All infants were divided into 3 groups based on their gestational age and 4 groups based on their birth weight. Fetal hemoglobin and ROP were compared between these groups. The infants were then categorized into ROP and no ROP groups based on International Classification for Retinopathy of Prematurity (ICROP), 2021. The relationship between gestational age, birth weight, fetal hemoglobin and ROP was evaluated. Results: A total of 410 preterm infants were included out of which 110 infants had ROP. Fetal Hb concentration was higher in 33-36 weeks when compared to lower gestational age showing a positive corelation with gestational age. Similarly, fetal Hb concentration was higher in birth weight 1.5-2 kg compared to lower birth weight showing a positive corelation. Infants with ROP had a significantly lower concentration of HbF, with gestational age and birth weight groups compared to infants without ROP. Conclusions: Lower gestational age, lower birth weight and lower concentration of HbF was found significantly associated with the development of ROP in preterm infants. Preterm infants have a positive corelation between fetal hemoglobin and gestational age/birth weight.